(untitled) (Bangladesh Journal of Psychiatry, 2020)
There is a dearth of studies related to consultation-liaison psychiatry in Bangladesh. The psychiatric referral rates in this country are very low, considering the higher rates of psychiatric morbidity in patients who attend various departments of a general hospital. This was a descriptive study consisting of all the cases referred for psychiatric consultation from inpatient units of various departments of BIRDEM General Hospital, Dhaka from July 2017 to June 2018. Patients of any age and of either gender were included. A total of 673 patients (1.97% of total admission) were referred from different departments of the hospital for psychiatric consultation within the study period. Majority of the respondents were female. The mean age of the respondents was 59.47 (±1.98) years. Among the referred, Generalized anxiety disorder (GAD) was the diagnosis in 24.96%, followed by Major depressive disorder (MDD) in 9.95% cases. Referral from the department of Medicine and allied was 92.86 %, followed by department of Surgery and allied (6.38%) & department of Obstetrics and Gynaecology (0.74%). Frequency of referral was the lowest in the months of November to January. There is a need to encourage multi-disciplinary interaction in the management of patients who attend general hospitals, so as to better identify the psychiatric morbidity. Bang J Psychiatry December 2017; 31(2): 38-42